Morphofunctional Distinction of Retinal Pigment Epithelium in Normal and Age-related Macular Degeneration. Review of the Literature - R. R. Fayzrakhmanov; E. D. Bosov; V. A. Bogdanova; E. E. Vaganova; O. L. Sekhina (Oftalʹmologiâ, 2024)
The retinal pigment epithelium performs a number of highly specialized functions. The relevance of studying morphological changes in the pigment epithelium is associated with an increase in the number of patients with age-related macular degeneration (AMD), polypoid choroidal vasculopathy (PCV), central serous retinopathy and retinitis pigmentosa. The increase in the number of patients with these pathologies is associated both with the general trend of aging of the world’s population and with modern opportunities for mass diagnostics. The pigment epithelium performs a number of functions that ensure the normal functioning of the retina. The main structural unit is a hexagonal epithelial cell with a large number of melanosomes containing the pigment melanin. Pathomorphological changes in the pigment leaf are an important indicator of the development of AMD. In most cases, an elevation or detachment is formed, in which three types are distinguished: druzenoid, fibrovascular (hemorrhagic) and serous. According to a prospective multicenter study, in 19 % of cases, the druzenoid form progresses into atrophy of the pigment epithelium. There are a number of studies that present harbingers of integrity damages. Fibrovascular detachment is the pathomorphological basis for the formation of submacular hemorrhage. The pathogenesis of serous exfoliation in AMD is associated with a range of different mechanisms, ranging from degenerative changes in the Bruch membrane to the formation of choroidal neovascularization. In the scientific publications of a number of authors, information is presented about the complication of detachment in the form of the development of a rupture of the retinal pigment epithelium. The key criterion for a threatening rupture is the height of the pigment leaf detachment. Damage of the integrity of the pigment leaf in the long term is a factor in reducing or complete loss of vision. This is especially characteristic when a gap is formed in the central area of the retina. Also, visual impairment is observed in cases of submacular hemorrhage and the formation of a fibrous scar. An important point, at present, is the development of protocols for the management of patients with ruptures on the background of the underlying disease.